Superior thermal stability in a high-strength Al–Zn–Mg–Cu–Si alloy via tailored precipitation sequence - Yuan-Ting Mo; X.Y. Xu; Ze-Tian Liu; Hai-Xiao Zhang; Cheng Wang; Xu Liu; Shen-Bao Jin; Hui-Yuan Wang (Materials Research Letters)
Here, a novel Al–Zn–Mg–Cu–Si alloy is developed, combining a high yield strength of ∼420 MPa with excellent thermal stability. This exceptional performance is achieved through a tailored precipitation sequence enabled by a multi-step aging strategy. The first aging step at 80 °C plays a crucial role in promoting the formation of dense Mg–Zn–(Cu) clusters. Ultimately, the Al alloy exhibits a high density of fine strengthening precipitates, while attaining a substantial density of thermally stable QP2 phases. This strategy overcomes the trade-off between strength and thermal stability, offering a promising approach for high-strength Al alloys.